THE ROLE OF INVESTMENT IN THE DEVELOPMENT OF THE NATIONAL ECONOMY (Conference Zone, 2021)
This article provides information on the role and place of investment in the development of the economy of the Republic of Uzbekistan and develops a number of scientific proposals to improve the industry.